Role of construction in economic development: Review of key concepts in the past 40 years - Dang, Giang (Elsevier, 2015)
This paper reviews the studies completed in the past four decades which examined the role of the construction industry in economic development. Findings from these studies demonstrated the significant relationship between the construction industry and economic growth in developing countries. These findings also suggested that the relationship appears to be more complicated than originally thought. It was noted that further expansion of the construction industry beyond the adaptive capacity of the economy will only waste national resources. Little is known about the impact that the adaptive capacities of other sectors in the economy have on the construction sector. This knowledge gap requires further study in order to formulate a more effective long-term strategy for construction industry development.